Jamaica : First Review Under the Stand-By Arrangement, Request for Waiver of a Performance Criterion, and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Jamaica's First Review under the Stand-by Arrangement (SBA), Request for Waiver of a Performance Criterion (PC), and Request for Modification of PC. Program implementation remains strong under the SBA. Sustained macroeconomic discipline and visible reforms have boosted stability and confidence. Positive real GDP growth has been recorded in seven consecutive quarters, and Jamaica is projected to grow 2 percent in fiscal year 2017/18, bolstered by construction and tourism, among other factors. Inflation reached an all-time low in 2016, and investor confidence is at an all-time high, attracting foreign direct investment. The current account deficit has narrowed significantly, supporting accumulation of nonborrowed reserves.